Analisis Retouching Foto Close Up Karya Petra Sinuraya Menggunakan Teknik Digital - Yesika Prebina Br. Bangun (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the concept and process of visualization of the close-up photo retouching technique by Petra Sinuraya. This research method is descriptive analytic research on the work. The subject of this type of research is Petra Sinuraya's close up photography retouching work. Data were analyzed descriptively analytic with percentage analysis using simple statistical procedures. Data obtained by using interview and documentation methods. The instrument was designed based on interview and documentation guidelines, and was developed based on situations that occurred in the field. The research was conducted by taking and selecting documents in the form of 10 pieces of art photos. The results showed that the close-up photo retouching process used by Petra Sinuraya was a digital technique by sharpening skills through the touch of tools available in Photoshop software. The role of composition in the retouching process is very important for client needs so that the photo looks more attractive in the final result. As for what Petra Sinuraya does in Close Up photo retouching is in various ways such as the Spot Hiling Brush for Smoothing the Skin, Burn and dodge tool for eye retouching, Dodge and Burn for Lightening / Darkening Contrast, filter noise and Gaussian blur - for flawless skin. and the Patch tool to enhance photos.